Communication—Effects of Oxygen Concentration Gradient on Resistive Switching Behavior in Oxygen Vacancy-Rich Electrodes. (10th February 2016) - Pan, Chih-Hung; Chang, Kuan-Chang; Chang, Ting-Chang; Tsai, Tsung-Ming; Zhang, Rui; Liang, Shu-Ping; Lin, Chih-Yang; Chen, Min-Chen; Chen, Po-Hsun; Syu, Yong-En; Huang, Hui-Chun; Sze, Simon M.
Abstract : In this letter, we demonstrate that the set and reset voltages of resistance random access memory (RRAM) are affected by the oxygen concentration gradient. Owing to higher oxygen ion storage ability in the ITO electrode, resistive switching behaviors will occur near the ITO electrode. During forming and set processes, oxygen ions will be propelled into the ITO electrode due to its oxygen vacancy-rich property. To investigate the effect of oxygen concentration gradient on resistive switching behaviors, electrical analysis of the characteristics of RRAM devices with different ITO thicknesses was performed, and a model was proposed to explain the phenomenon.